A constituição das psicoses na teoria freudiana - Souza, Josiane Rodrigues (Universidade Federal de São Carlos, 2023)
This study aims to investigate the formation of the theory of psychoses in Freud. Thus, in the first part of our research, we present aspects that demonstrate that the question of the genesis of psychoses is embedded in Freud's early investigations, starting from the phenomena of paranoia and hallucinatory confusion. Consequently, we highlight how the association between the origin of paranoia, the development of libido, and the concept of narcissism based on the Schreber Case assumes an important role within the theory of psychoses. Moving forward, our focus revolves around the analysis of the specificities that comprise the defense mechanism of psychoses and its conceptual reverberations concerning the rupture of the ego with objective reality, in light of the theorization of the second topic. Finally, we then propose a reflection on the relationship between psychoses and psychoanalytic treatment, drawing from certain concepts elements addressed throughout our research, which include the libidinal economy, the interplay between the death drive and psychoses, as well as the weakening of Ego (Ich) functions, with the aim of supporting the hypothesis that the economic expenditure of psychoses is an important key to understanding some of the impasses related to the psychoanalytic treatment of these cases.
The constitution of psychoses in freudian theory
Keywords: Freud; Neurose; Psicose; Tratamento Psicanalítico; Freud; Neurosis; Psychosis; Psychoanalytic Treatment; CIENCIAS HUMANAS::FILOSOFIA::EPISTEMOLOGIA